2023
DOI: 10.1186/s12913-023-10361-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the implementation of digital-supported interventions for the secondary prevention of heart disease: a systematic review using the RE-AIM planning and evaluation framework

Caroline de Moel-Mandel,
Chris Lynch,
Ayuba Issaka
et al.

Abstract: Background mHealth technologies are now widely utilised to support the delivery of secondary prevention programs in heart disease. Interventions with mHealth included have shown a similar efficacy and safety to conventional programs with improvements in access and adherence. However, questions remain regarding the successful wider implementation of digital-supported programs. By applying the Reach-Effectiveness-Adoption-Implementation-Maintenance (RE-AIM) framework to a systematic review and me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
0
0
Order By: Relevance
“…Systematic reviews of the implementation of mHealth technologies using the RE-AIM framework, however, have been conducted in other disease areas. In an extension to a systematic review of the effectiveness of digital-supported programmes for heart disease, authors reported on RE-AIM indicators from 36 publications (27 studies) [85]. They found few studies reported on maintenance and information on intervention fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of the implementation of mHealth technologies using the RE-AIM framework, however, have been conducted in other disease areas. In an extension to a systematic review of the effectiveness of digital-supported programmes for heart disease, authors reported on RE-AIM indicators from 36 publications (27 studies) [85]. They found few studies reported on maintenance and information on intervention fidelity.…”
Section: Discussionmentioning
confidence: 99%